2016
DOI: 10.1186/s12870-016-0710-y
|View full text |Cite
|
Sign up to set email alerts
|

Geographical distribution of genetic diversity in Secale landrace and wild accessions

Abstract: BackgroundRye, Secale cereale L., has historically been a crop of major importance and is still a key cereal in many parts of Europe. Single populations of cultivated rye have been shown to capture a large proportion of the genetic diversity present in the species, but the distribution of genetic diversity in subspecies and across geographical areas is largely unknown. Here we explore the structure of genetic diversity in landrace rye and relate it to that of wild and feral relatives.ResultsA total of 567 SNPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
65
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 69 publications
10
65
3
Order By: Relevance
“…Similar results were obtained by Hagenblad et al. () who found limited genetic clustering according to taxonomy below the species level. All our samples have been maintained in ex situ genebank collections for at least one decade, some even since the 1940s.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similar results were obtained by Hagenblad et al. () who found limited genetic clustering according to taxonomy below the species level. All our samples have been maintained in ex situ genebank collections for at least one decade, some even since the 1940s.…”
Section: Discussionsupporting
confidence: 90%
“…Hagenblad et al. () used a SNP array with 576 features to genotype a panel of S. cereale , S. cereale subsp. vavilovii , and S. strictum genebank accessions and found that they likely underestimated diversity in S. strictum because the discovery panel comprised only domesticated rye.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hagenblad et al (2016) linked its distinctiveness with historical human migrations, since Finnish farmers settled after leaving their native country in the sixteenth century (Ahokas, 2008). Considering Portuguese historic trading markets it cannot be ruled out a scenario of multiple rye introductions into Portuguese territory, especially from Northern Europe (i.e., Sweden).…”
Section: Discussionmentioning
confidence: 99%
“…Landraces are plant populations which are cultivated by local farmers that have historic origin, unique identity with no any formal crop improvement (Prasanna, 2012;Hagenblad et al, 2016). They are often endowed with diverse genetic inheritance (Zeven, 1998) as well as local adaption and strong connection to traditional farming systems (Camacho-Villa et al, 2005).…”
Section: Importance Of Landracesmentioning
confidence: 99%